2018
DOI: 10.1038/s41467-018-07590-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a potent HMG-CoA reductase degrader that eliminates statin-induced reductase accumulation and lowers cholesterol

Abstract: Statins are inhibitors of HMG-CoA reductase, the rate-limiting enzyme of cholesterol biosynthesis, and have been clinically used to treat cardiovascular disease. However, a paradoxical increase of reductase protein following statin treatment may attenuate the effect and increase the side effects. Here we present a previously unexplored strategy to alleviate statin-induced reductase accumulation by inducing its degradation. Inspired by the observations that cholesterol intermediates trigger reductase degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 69 publications
(87 reference statements)
6
85
0
2
Order By: Relevance
“…Importantly, the sterol regulatory network that governs HMGCR levels has been confirmed to be functional in vivo in mouse models. Knockout of gp78 stabilizes HMGCR and upregulates its activity in mouse liver (58), whilst intake of dimethylated sterol analogues leads to depletion of hepatic HMGCR and reduced serum cholesterol (59). Furthermore, levels of a transgenic protein comprising the sterol-sensing domain of HMGCR are increased or decreased by statin or cholesterol feeding, respectively (60), in agreement with previous cell culture experiments (52).…”
Section: The Classic Control Enzyme -Hmgcrsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, the sterol regulatory network that governs HMGCR levels has been confirmed to be functional in vivo in mouse models. Knockout of gp78 stabilizes HMGCR and upregulates its activity in mouse liver (58), whilst intake of dimethylated sterol analogues leads to depletion of hepatic HMGCR and reduced serum cholesterol (59). Furthermore, levels of a transgenic protein comprising the sterol-sensing domain of HMGCR are increased or decreased by statin or cholesterol feeding, respectively (60), in agreement with previous cell culture experiments (52).…”
Section: The Classic Control Enzyme -Hmgcrsupporting
confidence: 84%
“…This collective understanding of sterol-induced HMGCR degradation will undoubtedly be of importance in the future development of cholesterol-lowering therapeutics. Such treatments may be useful in augmenting or substituting statins, which can lose efficacy over time or lead to severe withdrawal effects (61) due to compensatory upregulation of HMGCR gene expression and a decline in degradation-promoting sterol intermediates (59).…”
Section: The Classic Control Enzyme -Hmgcrmentioning
confidence: 99%
“…We found that exogenously added lanosterol, 24,25-dihydrolanosterol (24,, or other 4,4-dimethylated sterols could stimulate HMGCR ubiquitination in vitro and HMGCR degradation in cultured cells (18). Recently, we developed a lanosterol derivative (named HMG499 or compound 81) that effectively degrades HMGCR in cultured cells and lowers diet-induced hypercholesterolemia in mice (27). Consistently, Nguyen et al (28) observed HMGCR degradation under hypoxia, a condition that causes lanosterol and 24,25-DHL accumulation because oxygens are indispensable for converting lanosterol to cholesterol.…”
mentioning
confidence: 99%
“…Insulin deficiency is associated with decreased HMG CoA/mevalonate ratio indicating increased enzyme activity. Numerous studies have highlighted that the activity of HMG-CoA reductase is increased in diabetic rats [22].…”
Section: Discussionmentioning
confidence: 99%